Effect of H2O2 Concentration on Morphology, Reflectivity and Wettability of Si Nanowalls Prepared by Metal Assisted Chemical Etching - Behara, Anil Kumar; R. N., Viswanath; Mathews, Tom (Asian Journal of Chemistry, 2023)
A facile and low cost method, metal assisted chemical etching was used to prepare silicon (Si) nanowalls atop the Si wafer, where the effect of etchant solution concentration (H2O2 concentration) on the morphology, reflectivity and wettability of the fabricated Si nanowalls is investigated. The morphological and structural studies by scanning and transmission electron microscopy revealed the Si nanowalls prepared at both low and high H2O2 concentration are smooth, nonporous and single crystalline, where the increase of H2O2 concentration only changes the morphology from isolated nanowall structure to agglomerated nanowall structure. The height of nanowalls also increases with increase in H2O2 concentration and follows a linear behaviour with an etching rate of 5697 nm/M. The reflectance study shows that the reflectance is extremely low over broad wavelength range (300-1100 nm) for Si nanowalls, compared to that of planar Si wafer. The increase of H2O2 concentration significantly changes the wavelength dependence of the reflectance spectrum. The wettability studies show that SiNWs prepared at low H2O2 concentration exhibit hydrophobicity in contrast to the hydrophilicity of planar Si wafer, where the increase of H2O2 concentration to very high value changes the hydrophobicity of SiNWs to hydrophilicity as similar to planar Si wafer.